GITR Promotes the Polarization of TFH-Like Cells in Helicobacter pylori-Positive Gastritis - Ming, Siqi; Yin, Huan; Li, Xingyu; Gong, Sitang; Zhang, Guoliang; Wu, Yongjian (Frontiers in Immunology, 2021)
Gastric CD4+T cells contribute to Helicobacter pylori (H. pylori)-induced gastritis by amplifying mucosal inflammation and exacerbating mucosal injuries. However, the pathogenic CD4+ T cell subset involved in the gastritis and potential regulators are still unclear. Here we identified an IL-21-producing gastric CD4+T cell subset, which exhibited tissue-resident CXCR5−BTLA−PD-1hi TFH-like phenotype in H. pylori positive gastritis patients. Meanwhile, we identified Glucocorticoid-induced tumour necrosis factor receptor (GITR) as an important regulator to facilitate IL-21 production by CD4+T cells and accelerate mucosal inflammation in gastritis patients with H. pylori infection. Moreover, GITR expression was increased in gastric CD4+T cells of gastritis patients compared to healthy controls, along with the up-regulated expression of its ligand GITRL in mucosal macrophages (M) of gastritis patients. Further observations showed that the activation of GITR/GITRL signal promoted IL-21 production of CD4+T cells via STAT3 pathway. Besides, IL-21 from CD4+T cells induced the proliferation of B cell and promoted the production of inflammatory cytokines IL-1 and IL-6, chemokines MIP-3 and CCL-25, as well as matrix metalloproteinase (MMP)-3 and MMP-9 by human gastric epithelial cells, suggesting the facilitating effect of IL-21-producing CD4+T cells on mucosal inflammation and injuries. Taken together, we revealed that GITR/GITRL signal promoted the polarization of mucosal IL-21 producing-CD4+T cells in H. pylori-positive gastritis, which may provide therapeutic strategies for clinical treatment of H. pylori-induced gastritis.